Prinsip Pendidikan Islam Moderat Dalam Al-Qur’an Surah Al-Baqarah Ayat 143 Dan Surah Al-Qalam Ayat 28 - Lailiyah, Asma’ul Izzatul; Farih, Muhammad (Universitas Yudharta Pasuruan, 2024)
The Qur'an characterizes the Muslim community as a wasat community. In this context, all actions and behaviors must reflect moderation. To achieve this attitude, more effort is needed because this attitude is not taken from granted. The development of Muslims, especially young people who are far from being moderate, is an indication that moderation is not well projected. To form this attitude, it is necessary to conceptualize how the Qur'an provides a logical structure in the attainment of becoming a wasat community. Among the verses of the Qur'an that discuss this topic are Q.S. Al-Baqarah verse 143 and Q.S. Al-Qalam verse 28. This structure can then be used to provide education and planting to the younger generation through education in schools. The approach used in this research is a qualitative approach with a type of library research. This study analyses the principles of moderate Islamic education in Q.S. Al-Baqarah Verse 143 and Q.S. Al-Qalam Verse 28. The results of this study indicate that the principles of moderate Islamic education in Q.S. Al-Baqarah Verse 143 namely balance and diversity principles in which these principles can be realized through an inculcation approach and a cognitive moral development approach. While the principle of moderate Islamic education in Q.S. Al-Qalam Verse 28 namely the principles of openness, balance, and integration in which these principles can be realized through a value analysis and clarification approach and an action learning approach.